Carotid Artery Stenting in Patients undergoing Emergency Intracranial Endovascular Therapy for Acute Stroke - Nofal, Sabih; Shiraz, Atif; Liaquat, Jahanzeb; Akhtar, Sohail; Abbas, Ghulam; Slehriya, Atiq Ur Rehman (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the outcomes of concurrent carotid artery stenting in patients undergoing emergency intravascular management for acute stroke. Study Design: Case Series Study. Place and Duration of Study: Department of Interventional Radiology, Armed Forces Institute of Radiology and Imaging, Rawalpindi Pakistan, from Mar 2020 to Mar 2021. Methodology: The study involved recruitment of patients undergoing emergency intracranial vascular intervention for Acute Ischemic Stroke, with concurrent ipsilateral carotid stenosis. Thrombus aspiration from the intracranial vessels was done with help of SOFIA Catheter. Following the confirmation of successful cerebral revascularization, the carotid lesion was stented using an appropriately sized stent. All patients were closely monitored for one year to assess any morbidity and mortality outcomes. Results: A total of 11 patients were included in this study out of which 8(72.7%) were male and 3(27.3%) were female. Mean age was 63.73+10.56 years. Hypertension was the most common co-morbid disease, 9(81.8%). The stenosis ranged from 58 - 94%. The residual stenosis after stenting was 11 – 40 %. Per-operatively, 2 patients (18.2%) had Cerebral Hyperperfusion and 1 (9.1%) had asymptomatic stent thrombosis. In terms of complications, there were a total of three (27.3%) CVA events in the study population at 1 years follow up. Two patients recovered and there was 1(9.1%) mortality. Conclusions: The initial experience in management of tandem stenosis of the carotid artery by stenting while performing thrombectomy of ipsilateral ischemic stroke has shown encouraging results.